Dissecting the Roles of PDCD4 in Breast Cancer - Cai, Qian; Yang, Hsin-Sheng; Li, Yi-Chen; Zhu, Jiang (Frontiers in Oncology, 2022)
Human programmed cell death 4 (PDCD4) gene was mapped at chromosome 10q24 and encoded PDCD4 protein containing 469 amino acids. PDCD4 has demonstrated to be a protein translation inhibitor and tumor suppressor, which expression frequently decreased in breast cancer. PDCD4 could block translation initiation complex by binding eIF4A with MA-3 domains or directly binding 5’ mRNA internal ribosome entry site with RNA binding domain to suppress breast cancer progression and proliferation. Numerous regulators and biological process including non-coding RNAs, proteasomes, estrogen, natural compounds or inflammation could control PDCD4 expression in breast cancer. Loss of PDCD4 expression was also responsible for drug resistance in breast cancer. HER2 activation downregulates PDCD4 expression via activating MAPK, AKT, and miR-21 in aromatase inhibitor resistant breast cancer cells. Moreover, modulating miRNA/PDCD4 axis maybe an effective strategy for overcoming chemoresistance in breast cancer. Down-regulation of PDCD4 was significantly associated with short overall survival of patients, suggested PDCD4 could be an independent prognostic marker for breast cancer.